Advertising as Information: An Empirical Note - Laband, David N. (The Review of Economics and Statistics, 1986)
Lamm, R. McFall, Unionism and Prices in the Food Retailing Industry, Journal of Labor Research 3 (Winter 1982), 69-79. Marion, Bruce W., Willard F. Mueller, Ronald W. Cotterill, Frederick E. Geithman, and John R. Schmelzer, Food Retailing Industrv': Market Structure, Profits, and Prices (New York: Praeger, 1979a). ______ The Price and Profit Performance of Leading Food Chains, A merican Journal of A gricultural Economics 61 (Aug. 1979b), 420-433. Salinger, Michael A., Tobin's q, Unionization, and the Concentration-Profits Relationship, Rand Journal of Economics 15 (Summer 1984), 159-170. Voos, Paula B., and Lawrence R. Mishel, Union Impact on Profits: Evidence from the Supermarket Industry, Working Paper No. 88, North Central Project 117, University of Wisconsin-Madison, Oct. 1985. The Union Impact on Profits: Evidence from Industry Price-Cost Margin Data, Journal of Labor Economics 4 (Jan. 1986), 105-133.